MicroRNA–mRNA Regulatory Network Associated with Cognitive Impairment in Multiple Sclerosis - Bruna De Felice; Federica Farinella; Giuseppe Romano; Concetta Montanino; Simona Bonavita; Deborah Archetto; Elisabetta Maida; Simona Raimo; Giacomo Lus; Maria Cropano; Cinzia Coppola; Elisabetta Signoriello (Molecular Neurobiology, 2026)
Cognitive impairment (CI) is a frequent and disabling manifestation of multiple sclerosis (MS), yet its molecular underpinnings remain poorly understood. This study aimed to identify microRNA (miRNA) signatures and related gene expression changes associated with CI in MS. Forty-six people with MS underwent clinical, radiological, and cognitive assessment. Peripheral blood mononuclear cells were collected for miRNA profiling using the miRCURY LNA miRNA Focus PCR Panel and validated through RT-qPCR. Experimentally validated miRNA target genes were retrieved using miRWalk with miRTarBase filtering. Target networks were constructed in Cytoscape, followed by protein–protein interaction analysis using STRING and functional enrichment analysis with database for annotation, visualization, and integrated discovery (DAVID) ( https://davidbioinformatics.nih.gov/ ). Selected target genes were further evaluated by gene expression analysis. The results showed that three miRNAs (i.e., miR-146a-5p, miR-let-7a-5p, and miR-21-5p) were significantly dysregulated in patients with MS with CI compared to those with preserved cognition. Gene expression analysis identified differential regulations of IL-1B, IL-6, SLC16A10, and NEFL, supporting the involvement of inflammatory and neurodegenerative pathways. Correlation analyses indicated specific miRNA–mRNA relationships underlying these alterations. These findings suggest that the combined dysregulation of miR-146a-5p and miR-21-5p, together with their target genes, constitutes a molecular signature associated with CI in MS. This profile could contribute to the development of miRNA-based biomarkers for early detection and monitoring of cognitive dysfunction in MS.

Correction to: Adiponectin in Cerebrospinal Fluid from Patients Affected by Multiple Sclerosis Is Correlated with the Progression and Severity of Disease - Elisabetta Signoriello; Marta Mallardo; Ersilia Nigro; Rita Polito; Sara Casertano; Andrea Di Pietro; Marcella Coletta; Maria Ludovica Monaco; Fabiana Rossi; Giacomo Lus; Aurora Daniele (Molecular Neurobiology, 2021)
A Correction to this paper has been published: 10.1007/s12035-021-02331-y

Adiponectin in Cerebrospinal Fluid from Patients Affected by Multiple Sclerosis Is Correlated with the Progression and Severity of Disease - Elisabetta Signoriello; Marta Mallardo; Ersilia Nigro; Rita Polito; Sara Casertano; Andrea Di Pietro; Marcella Coletta; Maria Ludovica Monaco; Fabiana Rossi; Giacomo Lus; Aurora Daniele (Molecular Neurobiology, 2021)
Adiponectin exerts relevant actions in immunity and is modulated in several disorders, such as multiple sclerosis (MS). In this study, we characterized adiponectin expression and profiles in cerebrospinal fluid (CSF) from MS patients to investigate its potential relationship with the severity and progression of the disease. Total adiponectin in CSF was measured by ELISA in 66 unrelated CSF MS patients and compared with 24 age- and sex-matched controls. Adiponectin oligomer profiles were analysed by Western blotting and FPLC chromatography. Total CSF adiponectin was significantly increased in MS patients compared with controls (9.91 ng/mL vs 6.02 ng/mL) ( p < 0.001). Interestingly, CSF adiponectin positively correlated with CSF IgG, and CSF/serum albumin directly correlated with CSF/serum adiponectin. Our data demonstrated that CSF adiponectin predicts a worse prognosis: patients with the progressive form of MS had higher levels compared with the relapsing remitting form; patients with higher EDSS at baseline and a higher MS severity score at 4.5-year follow-up had significantly elevated adiponectin levels with respect to patients with a less severe phenotype. Finally, the adiponectin oligomerization profile was altered in CSF from MS patients, with a significant increase in HMW and MMW. The correlation of CSF adiponectin with the severity and prognosis of MS disease confirmed the role of this adipokine in the inflammatory/immune processes of MS and suggested its use as a complementary tool to assess the severity, progression and prognosis of the disease. Further studies on larger MS cohorts are needed to clarify the contribution of adiponectin to the etiopathogenesis of MS.